Comparison of patterns of laxative ingestion to improve bowel preparation for colonoscopy: a pilot randomized clinical trial - Laiyemo, Adeyinka O.; Idowu, Kolapo A.; Burnside, Clinton; Williams, Carla D.; Jack, Momodu; Mekasha, Getachew; Ashktorab, Hassan; Brim, Hassan; Lee, Edward L.; Sanderson, Andrew K.; Kibreab, Angesom; Kwagyan, John (Endoscopy International Open, 2020)
Background and study aims Negative experiences with bowel preparation are a barrier to uptake of colonoscopy. The aim of this study was to examine the impact of different flavoring of polyethylene glycol (PEG) laxatives on patient satisfaction with and adequacy of bowel preparation during colonoscopy.Patients and methods This was a single-blind (endoscopist), parallel design, randomized trial (NCT 02062112) during which patients scheduled for colonoscopy were assigned to one of three groups: Group 1 (no laxative flavoring, n = 84); Group 2 (flavored entire laxative, n = 90) and Group 3 (tasted PEG with and without flavoring and decided how they want to drink the rest of the laxatives (choice group), n = 82). Patients rated their bowel preparation experience (satisfaction) and endoscopists accessed adequacy of bowel preparation during colonoscopy.Results There were no differences in patient ratings across the groups (1, 2 and 3) in taste of the laxatives (P = 0.67), ease of drinking (P = 0.53), and overall experience of bowel preparation process (P = 0.18). However, higher percentage of patients in the choice group would want the same laxative again if they were going to have a repeat colonoscopy in the future (72.5 % vs 81.3 % vs 88.9 %, P = 0.04). Surprisingly, adequacy of bowel preparation was highest among patients who drank their PEG unflavored (89.3 % vs 80 % vs 75.5 %, P = 0.07) and the had highest rates of adenoma detection (40.5 % vs 23.3 vs 39.0, P = 0.03).Conclusions There were no differences in overall tolerability of bowel preparation by patterns of flavoring of PEG. Those who drank unflavored PEG were less satisfied but had better clinical outcome, suggesting minimum justification effect in bowel preparation process.